2020
DOI: 10.1177/1120672120915169
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold yellow micropulse laser for treatment of diabetic macular edema: Comparison between fixed and variable treatment regimen

Abstract: Purpose: To compare the efficacy between fixed and variable treatment regimens of subthreshold yellow micropulse laser for the treatment of diabetic macular edema. Methods: This is a retrospective, comparative, 12-month study of 39 eyes: 24 eyes received fixed treatment regimen of subthreshold micropulse laser treatment and 15 eyes underwent variable treatment regimen of subthreshold micropulse laser, all eyes were followed up for 12 months. Subthreshold micropulse laser was performed with the following parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…[1][2][3][4][5][6] SMPL does not induce protein coagulation, and, therefore, prevents formation of retinal scars and tissue damage. 1,7 Even if SMPL has proven to be an effective treatment for diabetic macular edema (DME), in terms of visual function improvement/stabilization and macular thickness decrease, 3,4,[8][9][10][11][12][13][14][15] the exact mechanism of action is still under investigation. Retinal pigment epithelium (RPE) has been considered the main target with the consequent release of "heat shock proteins" (Hsps), in particular Hsp 70.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] SMPL does not induce protein coagulation, and, therefore, prevents formation of retinal scars and tissue damage. 1,7 Even if SMPL has proven to be an effective treatment for diabetic macular edema (DME), in terms of visual function improvement/stabilization and macular thickness decrease, 3,4,[8][9][10][11][12][13][14][15] the exact mechanism of action is still under investigation. Retinal pigment epithelium (RPE) has been considered the main target with the consequent release of "heat shock proteins" (Hsps), in particular Hsp 70.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical effects of SMPL on the retina in eyes with DME have been evaluated using standard imaging techniques, such as color fundus photography, optical coherence tomography (OCT), fundus autofluorescence (FAF), fluorescein angiography (FFA), and microperimetry. 3 , 4 , 9 11 , 15 However, only one study reported on the use of OCT angiography (OCTA) in evaluating microvascular changes occurring after SMPL treatment in DME. 18 In that study, our group documented early significant changes in some microvascular parameters (decrease in the area of FAZ, number of microaneurysms (MAs), and intraretinal area of cysts), in particular in the deep capillary plexus (DCP), during 6 months of follow-up after SMPL.…”
Section: Introductionmentioning
confidence: 99%
“…The cornerstones of subthreshold retinal laser therapy were established and defined using an 810-nm near-infrared micropulse laser [ 15 , 16 ]. The 577-nm yellow laser was later introduced and, although at present it is the most commercially available device, its efficacy has been evaluated by fewer studies involving smaller sample sizes and shorter follow-up periods [ 9 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. At present, a wide array of different duty cycle durations, spot sizes and power settings are employed by different clinicians, limiting, in our opinion, the diffuse clinical application of this technique [ 4 , 9 , 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis compared fixed parameters treatment and titrated treatment for 577-nm yellow laser: the first one was recommended based on its greater speed of setup and the implicit avoidance of any possibility of titration errors [ 13 ]. Titration has also been discouraged due to the absence of any reliable, safe and scientifically-validated titration algorithms [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation